Comparison of planned menus and centre characteristics with foods and beverages served in New York City child-care centres. Issue 15 (10th June 2016) - Breck, Andrew; Dixon, L Beth; Kettel Khan, Laura
Abstract: Objective: The present study evaluated the extent to which child-care centre menus prepared in advance correspond with food and beverage items served to children. The authors identified centre and staff characteristics that were associated with matches between menus and what was served. Design: Menus were collected from ninety-five centres in New York City (NYC). Direct observation of foods and beverages served to children were conducted during 524 meal and snack times at these centres between April and June 2010, as part of a larger study designed to determine compliance of child-care centres with city health department regulations for nutrition. Setting: Child-care centres were located in low-income neighbourhoods in NYC. Results: Overall, 87 % of the foods and beverages listed on the menus or allowed as substitutions were served. Menu items matched with foods and beverages served for all major food groups by >60 %. Sweets and water had lower match percentages (40 and 32 %, respectively), but water was served 68 % of the time when it was not listed on the menu. The staff person making the food and purchasing decisions predicted the match between the planned or substituted items on the menus and the foods and beverages served. Conclusions: In the present study, child-care centre menus included most foods and beverages served to children. Menus planned in advance have potential to be used to inform parents about which child-care centre to send their child or what foods and beverages their enrolled children will be offered throughout the day.